2006
DOI: 10.1021/jf060052t
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-free Lipase-Catalyzed Preparation of Long-Chain Alkyl Phenylpropanoates and Phenylpropyl Alkanoates

Abstract: An enzymatic method was developed for the preparation of medium- or long-chain alkyl 3-phenylpropenoates (alkyl cinnamates), particularly alkyl hydroxy- and methoxy-substituted cinnamates such as oleyl p-coumarate and oleyl ferulate. The various alkyl cinnamates were formed in high to moderate yield by lipase-catalyzed esterification of cinnamic acid and its analogues with fatty alcohols in vacuo at moderate temperatures in the absence of drying agents and solvents. Immobilized Candida antarctica lipase B was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
35
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 46 publications
7
35
0
Order By: Relevance
“…Cinnamic acid, 3-phenyl-2-propenoic acid, is an unsubstituted phenylpropanoid with limited antioxidant capacity. Previous studies reported the chemical and biocatalytic synthesis of cinnamoyl esters and glycerols [9,10]. A recent work examined the kinetics of chemical esterification of glycerol with cinnamic acid and its derivatives [11].…”
Section: Introductionmentioning
confidence: 99%
“…Cinnamic acid, 3-phenyl-2-propenoic acid, is an unsubstituted phenylpropanoid with limited antioxidant capacity. Previous studies reported the chemical and biocatalytic synthesis of cinnamoyl esters and glycerols [9,10]. A recent work examined the kinetics of chemical esterification of glycerol with cinnamic acid and its derivatives [11].…”
Section: Introductionmentioning
confidence: 99%
“…4. In previous studies [5][6][7][8][21][22][23][24], different phenolic acids from cinnamic series have been used for esterification in various media. It was found esterification was possible for the phenolic acids which the aromatic cycle was not parahydroxylated and the side chain was saturated.…”
Section: Effect Of Substrate Concentrationmentioning
confidence: 99%
“…However, most of phenolic acids are hydrophilic compounds and can mainly confer their functional properties or health effects in aqueous environments or water compartments [4]. Therefore, to apply natural phenolic acids in lipophilic formulation and processing, lipophilization is needed where enzymatic esterification with alcohols has proved itself to be a promising approach [5][6][7][8].…”
mentioning
confidence: 99%
“…In an early study, C. rugosa lipase was compared to other lipases on different cinnamic acid derivatives, showing 8% conversion to 1‐octanol in 12 days for ferulic acid in solvent‐free system . Later on, applying C. rugosa lipase in solvent‐free condition under reduced pressure (80 kPa) for the esterification of 4‐methoxycinnamic acid with oleyl alcohol lead to no or very low‐esterification activity . However, also a reasonable conversion of 26% has been reported for the transesterification of ethyl ferulate with tributyrin in toluene in 4 days .…”
Section: Introductionmentioning
confidence: 99%